The neuroscience of birth - and the case for Zero Separation - Nils J. Bergman (AOSIS, 2014)
Currently, Western maternal and neonatal care are to a large extent based on routine separation of mother and infant. It is argued that there is no scientific rationale for this practice and a body of new knowledge now exists that makes a case for Zero Separation of mother and newborn. For the infant, the promotion of Zero Separation is based on the need for maternal sensory inputs that regulate the physiology of the newborn. There are harmful effects of dysregulation and subsequent epigenetic changes caused by separation. Skin-to-skin contact is the antithesis to such separation; the mother's body is the biologically 'normal' place of care, supporting better outcomes both for normal healthy babies and for the smallest preterm infants. In the mother, there are needed neural processes that ensure enhanced reproductive fitness, including behavioural changes (e.g. bonding and protection) and improved lactation, which are supported by the practice of Zero Separation. Zero Separation of mother and newborn should thus be maintained at all costs within health services.